The Sociology of Community Connections - Bruhn, John G. (Springer US : Imprint: Springer, 2005)
Intervention to bring about beneficial social change is the theme of this second edition of Sociological Practice. Written for upper division and graduate students interested in careers in sociological practice or applied sociology, the authors show how sociological theories and methods can be used in intervening to solve or prevent current social problems. The books include Applications, Tables, and Figures to expand upon and illustrate the narrative text. Changes to this edition include up to date coverage of all topics including a new chapter on multifactor multilevel problem solving.